2021
DOI: 10.3389/fpsyg.2021.767876
|View full text |Cite
|
Sign up to set email alerts
|

How Live Streaming Features Impact Consumers’ Purchase Intention in the Context of Cross-Border E-Commerce? A Research Based on SOR Theory

Abstract: Given that “cross-border e-commerce + live streaming” has become an important driver of global trade but limited attention has been paid to this area, this study examines the impacts of live streaming features on the consumers’ cross-border purchase intention from the perspectives of consumers’ overall perceived value and overall perceived uncertainty based on the SOR theory. In addition, through investigating the moderating effects of saving money, this study reveals the impacts of amazing bargains in live st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…The use of the S-O-R theory as a theoretical framework for this research is advantageous for two reasons. First, this model provides the theoretical basis for the understanding of consumer behavior and has been widely applied to examine consumers' behaviors in e-commerce, such as purchase intention (Guo et al, 2021 ), online repurchase intention (Zhu et al, 2020 ), and impulse buying behaviors (Chen and Yao, 2018 ). Second, the S-O-R theory allows us to capture the unique dimensions of real-time social interaction in live-streaming e-commerce and construct a dynamic mechanism to present how LSI influences customer purchase intentions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the S-O-R theory as a theoretical framework for this research is advantageous for two reasons. First, this model provides the theoretical basis for the understanding of consumer behavior and has been widely applied to examine consumers' behaviors in e-commerce, such as purchase intention (Guo et al, 2021 ), online repurchase intention (Zhu et al, 2020 ), and impulse buying behaviors (Chen and Yao, 2018 ). Second, the S-O-R theory allows us to capture the unique dimensions of real-time social interaction in live-streaming e-commerce and construct a dynamic mechanism to present how LSI influences customer purchase intentions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The commercial application of next-generation information technology has brought wide-ranging business changes, and the touch points of customer experience have expanded from limited offline stores to the digital space (Hoyer et al, 2020 ). Live streaming, as novel information technology, has been an embedded live function of e-commerce platforms that are operated by mainstream e-commerce enterprises, such as Taobao.com and Jingdong.com (Wongkitrungrueng and Assarut, 2018 ; Cunningham et al, 2019 ; Sun et al, 2019 ; Park and Lin, 2020 ; Xu and Ye, 2020 ; Guo et al, 2021 ). Compared with traditional e-commerce, live-streaming e-commerce has become appealing to marketers because of its powerful interactions (Hu and Chaudhry, 2020 ; Kang et al, 2020 ; Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2020) proved that the live video streaming (LVS) strategy can improve customers' online purchase intention by providing more authentic information to reduce psychological distance and uncertainty. Guo et al (2021a) and Baek et al (2020) confirmed the positive effect of live streaming features on reducing consumers' overall perceived uncertainty, and increasing consumers' overall perceived value and purchase intention in the context of cross-border e-commerce.…”
Section: Authenticitymentioning
confidence: 65%
“…The literature related to purchase behavior in the livestreaming environment usually pays attention to stimuli and responses, but the internal mechanism of impulse buying remains unclear. According to Guo et al (2021) , livestreaming features greatly boost consumers’ overall perceived value and purchase intention. Lu and Chen (2021) found that livestreaming hosts’ physical attributes, conveyed through vicarious product trials and values shared via instant engagement, enable consumers with similar physical traits and values to reduce product uncertainty and cultivate trust.…”
Section: Introductionmentioning
confidence: 99%